'Why Do They Talk about Spirits?': Anthropological Interventions in Classroom Settings with Latin@ Immigrant Students. (1st December 2013) - ,
Abstract : This article describes the author's experiences as a professor in a Bilingual Education Programme at a local university; students are public school teachers in North Texas, teaching in classrooms ranging from 80 to 95 per cent Latin@ students. The author uses multi-sited ethnography and history in order to set the scenario for the political, ideological and economic factors embedded in the understanding of the Latin@ immigrant community presence in the area. The article documents anthropological 'intervention' strategies through papers and research projects. Students (public school teachers) are required to exercise participatory approaches to engage their own Latin@ students in their research papers. Through analysis of the transformative research projects presented by the students, the author documents the power of anthropological intervention and the effects in education policy.